2017
DOI: 10.21608/jfds.2017.38714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Frozen Storage on the Chemical, Physical and Microbiological Quality of Imported Mackerel (Scomber scombrus).

Abstract: The imported frozen (Mackerel) Scomber scombrus was evaluated for the changes of its quality during freezing storage at -18ºC for four months and its compliance with the Egyptian standard specifications. It was found that the protein, lipid and ash contents decreased during the storage period. Furthermore, moisture slightly increased during the storage period. The results also indicated that the samples did not exceed the permissible limits of total nitrogen as determined by the Egyptian Organization for Stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
4
4
0
Order By: Relevance
“…In this study, the pH values of the HMR product ranged from 5.97 ± 0.07 to 6.07 ± 0.03 within 90 days of frozen storage, comparable to the pH values of fresh fish, which varies from 5.5 to 6.6 [39]. The pH values were consistent with the findings reported by El-Dengawy et al [40], in which frozen mackerel increased their pH values from 5.96-6.20 after 4 months of storage. Lipid oxidation of the HMR products was detected using TBARS analysis.…”
Section: Chemical Properties Of Braised Mackerel With Radishsupporting
confidence: 91%
“…In this study, the pH values of the HMR product ranged from 5.97 ± 0.07 to 6.07 ± 0.03 within 90 days of frozen storage, comparable to the pH values of fresh fish, which varies from 5.5 to 6.6 [39]. The pH values were consistent with the findings reported by El-Dengawy et al [40], in which frozen mackerel increased their pH values from 5.96-6.20 after 4 months of storage. Lipid oxidation of the HMR products was detected using TBARS analysis.…”
Section: Chemical Properties Of Braised Mackerel With Radishsupporting
confidence: 91%
“…This indicates that frozen storage (-18°C) period up to 12 months stands behind spoilage of fish and protein degradation. The rise in TVN during frozen storage was a result of microbial action on non-protein and protein nitrogenous compounds (Viji et al, 2015;El-Dengawy et al, 2017).…”
Section: Changes In Physicochemical Propertiesmentioning
confidence: 99%
“…The decrease in the level of TBARS in fish burgers affected by cooking techniques can be caused by the interaction between malonaldehyde and protein breakdown products to produce tertiary compounds (Hernandez-Herrero et al, 1999). According to Taskaya et al, (2003); Tokur et al, (2004); Mahmoudzadeh et al, (2010);Vanitha et al, (2015);and El-Dengawy et al, (2017) who observed the similar pattern of data on fish burgers, these findings are consistent.…”
Section: Chemical Analysis Chemical Composition Of Fish Burgersmentioning
confidence: 57%